Numerical investigation of VIV responses of the flexible riser system modelled as tensioned cable subjected to shear flow. (1st December 2022) - Prethiv Kumar, R.; Nallayarasu, S.
Abstract: The crossflow vortex-induced vibration (VIV) responses of the tensioned cable subjected to the sheared flow velocity profile are investigated numerically using the wake oscillator model. A comparative study is carried out on the VIV response characteristics between the tensioned cable and beam with an aspect ratio ( L/D ) of 3000. The study was conducted on tensioned cable having different L/D of 2000 and 3000 achieved by varying both diameter and length of the cable. The effect of top tension on the RMS crossflow displacement responses is investigated. The RMS crossflow displacement response is not sensitive to the boundary conditions for the flexible cylinder modeled as a tensioned cable. In contrast, the RMS crossflow displacement response of the lower L/D flexible cylinder modeled as a beam is sensitive to boundary conditions. The standing wave response pattern is observed for the beam with L/D of 500. The standing and traveling wave response patterns are combined for the tensioned cable with L/D = 500. Unlike finite tensioned beams, the higher mode responses are obtained even in the lower aspect ratio for tensioned cables. Highlights: The VIV response of tensioned cable subjected to sheared flow is investigated using the wake oscillator model. The effect of aspect ratio, top axial tension, and boundary conditions was investigated. A comparative study was carried out using flexible riser modeled as tensioned cable and beam.